Prevalence and associated factors of immunization among under-five children in Somalia - Denekew Bitew Belay; Mahad Ibrahim Ali; Ding-Geng Chen; Umalkhair Abdi Jama (BMC Public Health)
Abstract Background Children worldwide can live lives free from various illnesses and disabilities due to vaccination. For instance, vaccination has eliminated smallpox, a deformative and frequently fatal illness that claimed an estimated 300 million lives in the twentieth century. However, due to a lack of access to immunization and other health services, 14.3 million infants in 2022 still did not receive their first dose of the Diphtheria-Tetanus-Pertussis (DTP) vaccine, and an additional 6.2 million received only a portion of the scheduled dose. This study aimed to assess prevalence and determinant factors of immunization among under-five children in Somalia using Somalia Health and Demographic Survey (SHDS) Data. Methods The study design was cross-sectional, utilizing the SHDS 2020 data. A total of 3916 under-five children who fulfilled the inclusion criteria were included in this study. Count regression models were employed to explore factors associated with the number of vaccinations received per child. Results In this study, 9.14% of children did not receive any vaccination during their childhood. Different candidate count regression models were compared. Using AIC and BIC, the Negative-binomial (NB) regression model was found to be the best fit. From this model, we found that women ages 20–24 (IRR = 1.192, 95% CI: 1.083, 1.313) and 25–29 (IRR = 1.180, 95% CI: 1.068, 1.305) had a higher number of vaccinations per child compared to women in the 15–19 age group. Women who attended primary education (IRR = 1.090, 95% CI: 1.034, 1.150) and secondary education (IRR = 1.157, 95% CI: 1.058, 1.266) had a higher number of vaccinations per child compared to uneducated women) also correlated with increased vaccination Parity (IRR = 1.090, 95% CI: 1.031–1.153), and wealth quantile (IRR = 1.110, 95% CI: 1.012, 1.217) positively influenced vaccination attendance. Regional disparities were also found to be significant, with Togdheer, Sool, Sanaag, Bari, Nugaal, Bay, Bakool, Mudug, Hiiraan and Galgaduud significantly different from Awdal region. In Negative-Binomial, age, region, residence, educational level, wealth quantile, child size at birth, parity and birth order emerged as key predictors, revealing complex determinants of vaccination utilization in Somalia. Conclusions A large proportion of children did not complete the full vaccination schedule. Socio-demographic factors, such as age, region, residence, educational level, wealth quantile, child size at birth, parity, and birth order, had a significant impact on the number of children vaccinated in Somalia. These findings underscore the importance of targeted interventions for addressing these factors. Implementing initiatives based on these conclusions has the potential to enhance vaccination coverage and child health outcomes.